Death Anxiety Among Online Loan Borrowers: A Psychological Perspective - Dewi, Ayu Marcelia Rahma; Rosyidi, Hamim; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Terror acts and intimidating behavior by debt collectors cause debtors to feel   fearful, anxious, and threatened, leading to mental health issues that can lead to death anxiety. The purpose of this study is to examine and determine how the effects of online lending can trigger death anxiety, as assessed using Irvin Yalom's perspective. The method used in this study is descriptive qualitative with a phenomenological approach to describe the problems and important elements of the information obtained from the two respondents. Based on the analysis conducted according to Yalom's theory, the fear of death can actually trigger change. Death anxiety in both respondents encouraged them to seek life goals, accept responsibility, and reorganize their lives in a healthier way. The problems faced by both respondents in this study involved coping strategies consisting of nine dimensions, including seeking information support, confronting, planned problem solving, seeking social support, maintaining emotional distance, escape, avoidance, self-control, and accepting responsibility, positive reappraisal. The threats felt by the respondents caused anxiety and excessive fear about their situation and the uncertainty of life in the future. This condition became one of the drivers for the formation of problem-solving strategies, where both respondents tried to find a way out so that the online loan issues could be resolved properly, allowing them to avoid being pursued by debt collectors.